Phlogopite/matrix, clinopyroxene/matrix and clinopyroxene/phlogopite trace-element partitioning in a calc-alkaline lamprophyre: new constrains from the Krizanovice minette dyke (Bohemian Massif) - Krmicek,L.; Halavinova,M.; Romer,R.L.; Vasinova Galiova,M.; Vaculovic,T. (Journal of Geosciences, 2014)
Mineral/matrix and mineral/mineral partition coefficients were determined for clinopyroxene and phlogopite phenocrysts and their very fine-grained (chilled) groundmass from a Variscan calc-alkaline (agpaitic index = 0.6) lamprophyre dyke of minette composition from the Bohemian Massif (Krizanovice, Tepla-Barrandian Unit). This dyke is characterized by high MgO (8.9 wt. %; Mg-number = 69) at intermediate SiO2 content (53 wt. %). The partition coefficients (D) between clinopyroxene and matrix were determined for 23 elements by laser ablation-inductively coupled plasma-mass spectrometry. Calculated phlogopite/matrixD values are very low, except for heavy rare earth elements (HREE) that range between 0.9 and 1.1. This suggests that HREE can be concentrated in clinopyroxene during crystallization from lamprophyre melt. In phlogopite, only 15 elements had contents above their respective detection limits. Phlogopite/matrix partition coefficients are on average higher than 1 (DBa = 1.1, DRb = 1.7 DTi = 1.5) and extremely low (≥ 0.02) for light rare earth elements (LREE). On the other hand, phlogopite/matrixD values for the majority of HREE could not be determined. Taken together, during simultaneous crystallization of clinopyroxene and phlogopite phenocrysts, Th, Zr, Hf, Y and LREE are preferentially partitioned into clinopyroxene and Ba with Rb and Ti into phlogopite.
Keywords: calc-alkaline lamprophyres; mineralogy; partition coefficients; Bohemian Massif